The Kabyle Rabbits (Algeria) - Berchiche M.; Kadi S.A. (Rabbit genetic resources in Mediterranean countries, 2002)
A description of the Algerian local population rabbit is carried out. Items that have been dealt with are: (i) a general description; (ii) climate and main features of its farming; and (iii) performance.